Three-dimensional finite element analysis of intramedullary nail with different materials in the treatment of intertrochanteric fractures. Issue 4 (April 2021) - Wang, Chenyan; Li, Xiaona; Chen, Weiyi; Wang, Changjiang; Guo, Yuan; Guo, Hongmei
Highlights: Finite element analysis was used to assess biomechanical behaviors of intramedullary nails. Polyetheretherketone (PEEK) intramedullary nails could effectively decrease stress shielding. Function-graded (FG) intramedullary nails have more advantages than metal implants. PEEK and FG intramedullary nails are promising alternatives to currently used metal implants. Abstract: Intramedullary nails are the common treatment options for femoral intertrochanteric fractures. However, aseptic loosening is considered to be one of the primary forms of failure that can be caused by the stress shielding between the bone and implants. The matching in mechanical properties of implant and bone is a key issue to prevent this failure. Polyetheretherketone (PEEK) and Function-graded (FG) materials are widely used in clinical because of their excellent mechanical properties. In this study, to investigate the biomechanical behaviors of intramedullary nails made of Ti-6Al-4V alloy, Stainless Steel (SS), PEEK and two FG materials, three-dimensional finite element models of intertrochanteric fracture femur with intramedullary nail were constructed with ABAQUS. The maximum von Mises stress on the femoral fracture surface fixed by PEEK intramedullary nail was the largest, followed by FG intramedullary nail, which help stimulate bone growth and subsequently reduce fracture healing time. Compared with traditional metal intramedullary nails, PEEK and FG implants might increase von Mises stress along the same path in the proximal femur. The results showed that PEEK and FG intramedullary nails obviously changed the stress distributions in the bone and reduced stress shielding. This finding indicated that PEEK and FG intramedullary nails have the potential to become alternatives to the conventional metal intramedullary nails.